Penerapan model pembelajaran active debate untuk meningkatkan keterampilan berbicara siswa kelas v sekolah dasar - Putri, Arifa Tiara; Poerwanti, Jenny Indrastoeti Siti; Saputri, Dwi Yuniasih (Universitas Sebelas Maret, 2025)
Speaking skills are skills that every individual must have. As with other skills, speaking skills need to be honed so that people can master them well. After online learning in 1st grade to 3rd grade, students are less competent in speaking. Therefore, action needs to be taken to improve students' speaking skills. There are several ways to improve speaking skills, one of which is by implementing the active debate learning model. The active debate learning model is an active learning model that involves two camps as a pro team and a con team. Learning with this model requires students to speak to convey their arguments. Research was conducted on the utilization of the active debate learning model, with the objective of enhancing students' speaking proficiency. This study was part of Classroom Action Research, employing the performance method. As the debate learning model begins, there are seven aspects of assessing students' speaking skills, they are: 1) courage to appear, 2) diction, 3) intonation, 4) volume, 5) articulation, 6) speaking fluency, and 7) understanding of the material. The results of research using the active debate learning model were that students' skills increased from 64.3% in cycle I to 82.14% in cycle II. Therefore, it can be inferred that implementing the active debate model has the potential to enhance students' oral communication abilities.